2013
DOI: 10.1007/s40544-013-0019-x
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium-based ionic liquids as novel lubricant additives for multiply alkylated cyclopentanes (MACs)

Abstract: Two lithium-based ionic liquids (ILs, L-C3N3, and L-P3N3) were synthesized and evaluated as novel lubricant additives for multiply alkylated cyclopentanes (MACs). They were found to be approximately 1.0% soluble in MACs at room temperature (RT), whereas traditional ILs, such as 1-ethyl-3-methylimidazolium tetrafluoroborate (L-B102), 1-hexyl-3-methylimidazolium hexafluorophosphate (L-P106), and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (L-F102), could not be dissolved in this base oil. Frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The apparent new peak of O1s on the worn scar lubricated by PE-OA-4% NOG (532 eV) could be ascribed to the -OH group [23]. Combined with the Fe2p and O1s spectra of worn scar lubricated by PE-OA-4% NOG, a robust and compact iron oxide film, likely consisting of Fe 2 O 3 , Fe(OH)O, FeOOH, FeO, and Fe 3 O 4 , was formed during the lubrication process [27][28][29]. In addition, the N1s peaks of NOG shifted to 399.6 and 400.5 eV after friction, which was ascribed to the formation of -C-N-group and nitrogen oxides or nitrates [30,31].…”
Section: Tribological Performance Of Peg400 Gel Lubricantsmentioning
confidence: 95%
“…The apparent new peak of O1s on the worn scar lubricated by PE-OA-4% NOG (532 eV) could be ascribed to the -OH group [23]. Combined with the Fe2p and O1s spectra of worn scar lubricated by PE-OA-4% NOG, a robust and compact iron oxide film, likely consisting of Fe 2 O 3 , Fe(OH)O, FeOOH, FeO, and Fe 3 O 4 , was formed during the lubrication process [27][28][29]. In addition, the N1s peaks of NOG shifted to 399.6 and 400.5 eV after friction, which was ascribed to the formation of -C-N-group and nitrogen oxides or nitrates [30,31].…”
Section: Tribological Performance Of Peg400 Gel Lubricantsmentioning
confidence: 95%
“…The molecular design is to introduce more tribochemical reactions that can inhibit oxidation and corrosion for better protection of base oils. It has been recently found that ionic liquids could be formed in base liquid in-situ by blending TFSILi with polyether and polyol ester [82][83][84][85]. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) can form ILs with synthetic esters, [Li(synthetic ester)]TFSI, by the donation of lone pairs on carbonyl oxygen atoms of an ester molecule to a lithium ion to form a weakly Lewis-acidic complex cation [Li(synthetic ester)] + and the following interaction with the weakly Lewisbasic anion TFSI − to generate [Li(synthetic ester)]TFSI.…”
Section: Ionic Liquids Additivesmentioning
confidence: 99%
“…MACs are composed of one cyclopentane ring with two to five alkyl groups substituted on the ring, and are synthesized by reacting dicyclopentadiene with alcohols of various chain lengths [62]. MACs consisting of a di-and tri-substituted (2-octylodecyl) cyclopentane ring possess potential applicability towards aerospace mechanisms and micro electromechanical systems (MEMS) due to their good chemical inertness, excellent viscosity properties, low volatility, low pour points and high thermal stability.…”
Section: Liquid Lubricantsmentioning
confidence: 99%